Kemampuan Peserta Didik Menarikan Tari Kipas Nyambai Bebai Di Sanggar Teluk Stabas - dewi rinjani; Dwiyana Habsary; Susi Wendhaningsih (Jurnal Seni dan Pembelajaran, 2019)
The Purpose of this Research is to knowing the Abilities of Student’s at Teluk Stabas Studio of Pesisir Barat Regency, for Hand-Held Fan “Nyambai Bebai” dancing. The kind of this research is descriptive qualitative which is using some research instruments such as, Observing, Interviewing and Documenting. The main data source for this research is the student of Teluk Stabas Studio. This research was conducted in eight meetings, and the used method was the Cooperative Learning Type Group Investigation. Based on the results of observation and assessment which is conducted on the last meeting can be concluded that the students in dancing of Hand-Held Fan “Nyambai Bebai” is really good or very skilled, The assessment criteria are taken based on The Movement Sequence, The Accuracy between Movement and Melody, and The Usage of Property. Therefore, the student can be categorized as capable in the dancing of Hand-Held Fan “Nyambai Bebai’ as learned at Teluk Stabas Studio of Pesisir Barat Regency. Penelitian ini dilakukan untuk mengetahui kemampuan peserta didik di sanggar Teluk Stabas kabupaten Pesisir Barat dalam menarian tari Kipas Nyambai Bebai. Jenis penelitianini merupakan deskriptif kulitatif. Instrumen penelitian observasi, wawancara, dan dukumentasi. Sumber data dalam penelitian adalah peserta didik di sanggar tari teluk stabas. Penelitian dilakukan selama delapan kali pertemuan,Metode yang digunakan adalah coperative learnig tipe group investigation. Hasil pengamatan dan penilaian dilakukan pada pertemuan kedelapan, dapat disimpulkan bahwa kemampuan peserta didik dalam menarikan tari Kipas Nyambai Bebai, dilihat secara keseluruhan dengan kriteria baik sekali untuk hafalan urutan gerak, untuk ketepatan gerak dengan iringan musik,dan penggunaan properti tari, dapat dikatakan baik. Sehingga peserta didik dapat dikategorikan mampu dalam menarikan tari kipas Nyambai Bebai seperti yang dipelajari di sanggar Tari Teluk Stabas Pesisir Barat.Kata kunci: Gambaran kemampuan, Cooverative group investigation, Tari Kipas Nyambai Bebai